Kemampuan Berpikir Divergen Siswa Berkebutuhan Khusus Tunagrahita Dalam Menyelesaikan Soal Matematika - Masamah, Ulfa; Agfiyah, Uzlifatul Izzah (Program Studi Tadris Matematika Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2024)
This research describes the divergent thinking abilities of mentally retarded students in solving mathematical problems involving the addition and subtraction of integer operations. The aspects studied include fluency, flexibility, and originality. This research is a case study research with a qualitative approach used on two mentally retarded students at SLB Rever Kids who were selected using purposive sampling. Data was obtained through tests, interviews and direct observation, explained using Polya stages and source triangulation. The data results show that S1 has potential in the aspects of fluency and originality, although it is less than optimal in accuracy and thoroughness. S2 experienced significant obstacles in all aspects, depending on teacher assistance due to difficulty reading and understanding the questions. The implications of this research emphasize the importance of visual and contextual-based learning strategies, such as visual aids and simple questions, to improve the divergent thinking abilities of students with intellectual disabilities. This research contributes to the development of inclusive learning according to the needs of students with special needs. ABSTRAK Penelitian ini mendeskripsikan kemampuan berpikir divergen siswa tunagrahita dalam menyelesaikan soal matematika operasi penjumlahan dan pengurangan bilangan bulat. Aspek yang diteliti meliputi fluency, flexibility, dan originality. Penelitian ini merupakan penelitian studi kasus dengan pendekatan kualitatif digunakan pada dua siswa tunagrahita di SLB Rever Kids yang dipilih secara purposive sampling. Data didapat melalui tes, wawancara, dan pengamatan langsung, dianalisis menggunakan tahapan Polya dan triangulasi sumber. Hasil data menunjukkan bahwa S1 memiliki potensi pada aspek kefasihan dan orisinalitas, meskipun kurang optimal dalam fleksibilitas dan ketelitian. S2 mengalami hambatan signifikan di semua aspek, bergantung pada bantuan guru akibat kesulitan membaca dan memahami soal. Implikasi penelitian ini menekankan pentingnya strategi pembelajaran berbasis visual dan kontekstual, seperti alat peraga dan soal sederhana, untuk meningkatkan kemampuan berpikir divergen siswa tunagrahita. Penelitian ini berkontribusi pada pengembangan pembelajaran inklusif sesuai kebutuhan siswa berkebutuhan khusus.